2010
DOI: 10.1093/bioinformatics/btq560
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating local population structure for fine mapping in genome-wide association studies

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 29 publications
3
71
1
Order By: Relevance
“…The proportion of SNPs with high |iHS| was the criterion used by Pickrell et al [9]. It has been suggested that genome-wide and locus-specific ancestries may show particular poor correlation at loci under selection compared to neutrally evolving loci [39]. We did not observe such a trend at loci with the highest iHS scores in either MEX AMR or MEX EUR .…”
Section: Methodscontrasting
confidence: 50%
“…The proportion of SNPs with high |iHS| was the criterion used by Pickrell et al [9]. It has been suggested that genome-wide and locus-specific ancestries may show particular poor correlation at loci under selection compared to neutrally evolving loci [39]. We did not observe such a trend at loci with the highest iHS scores in either MEX AMR or MEX EUR .…”
Section: Methodscontrasting
confidence: 50%
“…However, our simulation studies indicate that when a causal variant is an AIM and has a strong admixture mapping signal, these tests can have inflated type I error rates under the null hypothesis H 02 at the null AIM SNPs that are in admixture LD but not in background LD with the causal variant. We noticed that similar results have also been reported in [13, 14]. When evaluating the type I error rate by simulation studies, Wang et al (2011) and Qin et al (2011) used models including a covariate of local ancestry to simulate the case-control status.…”
Section: Discussionsupporting
confidence: 84%
“…To correct for the confounding effect of admixture LD in local regions and therefore map causal variants into small regions with a few hundred Kbs, association tests that adjust for local ancestries have been developed [13, 14]. However, these methods can have relatively low power in detecting causal variants with admixture mapping signals.…”
Section: Introductionmentioning
confidence: 99%
“…For our models, the mixing parameter α was set equal to 0.95 to accommodate linkage disequilibrium (LD), while the penalty parameter λ was selected based upon 10-fold cross-validation of the mean-squared prediction error. Age, sex, and the originally identified SNP were included as unpenalized covariates, with the previously used PCs capturing population stratification excluded from this and all further regression analyses due to the poor correlation between global and local ancestry (Qin et al 2010). SNPs were modeled under an additive genetic model and missing genotypes imputed with mean observed values.…”
Section: Methodsmentioning
confidence: 99%